Professional self-realization of elementary school teachers: definitive ANALYSIS OF THE CONCEPT - Olha V. Lebid; Liudmyla V. Tsurkan (Вісник Університету імені Альфреда Нобеля. Серія Педагогіка і психология, 2021)
The article makes a definitive analysis of the conceptual construct “professional self-realization of primary school teachers”. In particular, the essence of the terms “self-realization”, “professional selfrealization” in the works of Ukrainian and foreign scholars is studied. The peculiarities of understanding and interpretation of the content of these definitions by researchers are analyzed. It is noted that the definition of “self-realization” is an interdisciplinary multifaceted concept, which in psychology is considered in the context of human self-consciousness; in philosophy – in self-improvement of the human spirit and body; in pedagogy – in the desire for the fullest possible manifestation of capabilities, inclinations, abilities, qualities; in acmeology – in the achievement of acme-peaks in any activity. Specific features and differences in approaches to the interpretation of the essence of professional self-realization and its role in the activities of primary school teachers are identified. The concept of “professional self-realization” in the article is defined as an important component in the path of professional development of an individual, through which the socio-psychological space of human functioning in the profession is implemented. It is established that the professional self-realization of primary school teachers is associated with the desire to become the best in the professional aspect, the organization of the educational process in the primary grades of general secondary education and the creation of conditions for each student. The scheme of interrelation of basic concepts of research on the problem of professional self-realization of the teacher of primary classes is constructed. Professional self-realization of a primary school teacher is considered as a complex, purposeful, multilevel process of gradual transformation of professional potential into reality by involvement in professional and pedagogical interaction that occurs throughout the life of the individual. Primary school teacher’s self-realization lies in the professional and personal growth, awareness of their actions, of themselves in society and in professional activities. Prospects for further study in this direction of the factors influencing the professional self-realization of primary school teachers are outlined.